PENGARUH TULISAN ERNEST PRAKASA MENGENAI DR ZAKIR NAIK DI TWITTER TERHADAP CITRA ERNEST PRAKASA DI DESA BOJONGGEDE - rio septian (Jurnal Komunikasi, 2019)
The aim of this study was to find out the effect of ernest prakasa’s Posts about Zakir Naik in Twitter toward his negative image in Bojonggede. The approach of this study was quantitative descriptive. To collect the data, the researcher used questionnaire adn in analyzing the data, the researcher used Parametric statistics of regression and correlation test. This research was conducted in Bojonggede and took 100 respondents  as the sample of the study.  After the evaluation has been conducted, it was found that there is a significant relationship between Ernest Prakasa's posts about DR Zakir Naik on twitter with his negative image in Bojonggede. The details is ; 71.7% claim that the negative image of Ernest Prakasa in Bojonggede because of his posts about Zakir Naik, and 28,3% of other factors.